Vocal Nodules: Evolution From Childhood to Postpuberty - Gramuglia, Andrea Joia [UNESP] (2025)
Objective: To analyze the behavior of vocal nodules from childhood to postpuberty. Methods: Adolescents aged 15 years or older who presented vocal nodules in childhood were included and underwent the same evaluations performed in childhood. They answered a questionnaire about vocal symptoms, treatments, habits, and vocal abuse. They were submitted to videolaryngoscopy, auditory-perceptual, and acoustic vocal assessments. Results: In total, 31 adolescents (15-18 years), 23 boys, eight girls, mean age in childhood and postpuberty: girls (10.25 ± 1.85, 16.75 ± 1.3); boys (10.08 ± 1.34, 15.95 ± 1.87), without statistical difference between childhood and postpuberty (P > 0.05). Symptoms: four boys (12.9%) and three girls (9.67%) maintained dysphonia postpuberty. Videolaryngoscopy: nodules were not detected after puberty. Minor alterations: hyperemia (n-2), edema (n-1), posterior glottic cleft (n-1), and microweb (n-1). Treatments: vocal therapy (n-18), microsurgery (n-8), and no treatment (n-5). There was a significant difference in the acoustic (maximum phonation time, f0, jitter, pitch perturbation quotient, shimmer, amplitude perturbation quotient, and Student t test) and acoustic perceptive parameters (Mann-Whitney rank sum test) between the moments (childhood and postpuberty). In the comparison between the treatments (Shapiro-Wilk and Kolmogorov-Smirnov tests) just for shimmer parameter, there was a statistical difference, being more significant in surgery and speech therapy. Conclusions: After puberty, we observed a reduction in vocal symptoms, as well as an improvement in videolaryngoscopic findings and in auditory and acoustic perceptive vocal parameters. In the comparison between the treatments just for shimmer parameter, there was a statistical difference, being more significant in surgery and speech therapy.